Uma análise dialógica sobre o romance O anjo do quarto dia, de Gilvan Lemos, em relação a textos bíblicos - Oliveira, Samuel Lira de (2011)
The current research stems from the author s didactic pedagogic experiences and his Língua Portuguesa and Literatura Brasileira classes concerning the intertextual and dialogical field since such professional experiences have excited his interested when he noticed excerpts from the Holy Bible in passages of the Pernambucano writer Gilvan Lemos novels. The knowledge of the Backhtinian theory about spoken of others person has also proportioned the motivation to his study intertextuality and dialoguecity make up relations which establish themselves between some characters and passages in Gilvan Lemos ―O Anjo do Quarto Dia (1981)‖. Ana, Codó, Tininha, Piranha, (characters in the book) are related to some characters in the Holy Bible: Jesus Christ, Mary, mother to Jesus, and Mary Magdalene (New Testament) and Job (Old Testament). In this sense the novel is conceived as a linguistic phenomenon. The aim is to do a study from the discursive and linguistic elements of the religious and literary domains as well as the lexicon relations and their association with the intertextuality which have been created around these words. The core of this research is to analyze the linguistic construction in a literary work. The religious and literary elements are present as a support to the linguistic study. Therefore, the literary work is taken as a linguistic phenomenon as well as the non literary statement (in the sense of ―belles lettrers‖). A reflection will be made on the Backtinian (1981/1997/2002/2003) dialogism in order to analyze passages in the book ― O Anjo do Quarto Dia‖. Analysis point out that some lexicon relations being constructed in the book, around key terms on the intertextuality , point at distinct speeches about how the biblical intertextuality is worked up in Gilvan Lemos works. In order to excite the study about intertextuality in the present research, some conceptions will be inserted from Julia Kristeva s reflections (1974). The following books from the Holy Bible will be sources of research: from the Old Testament: Genesis, Exodus, Deuteronomy, 1 Samuel, 1 Kings, Job, Psalms, Ecclesiastes, Salomon s The song of songs, Isaiah, Jeremiah, Ezekiel, Daniel, Jonah, Habakkuk; from the New Testament ; Mathew, Mark, Luke, John, Acts, Romans, 1st Corinthians, Galatians, Colossians, 1st Timothy, Hebrews, Revelations; as well as Bazerman s (2007), Machado (1995), Beth Brait (1997) and Blickstein s (2000) studies about intertextuality whose emphasis is the effective presence of a text within another text